GROWTH AND YIELD OF BAJRA HYBRID AS INFLUENCED BY SPACING AND NITROGEN LEVELS IN RAINFED ALFISOLS - C. RADHA KUMARI, P. SHANTHI, M. NIVEDITHA, K.V.S. SUDHEER AND B. SAHADEVA REDDY (The Journal of Research ANGRAU, 2015)
A field experiment was conducted to study the response of bajra hybrid (ABH-1) to spacing and nitrogen levelsin alfisols of scarce rainfall zone under rainfed conditions during kharif, 2015-16 at Agricultural Research Station,Ananthapur. The experiment was laid out in Factorial Randomized Block Design and replicated thrice. The resultsrevealed that bajra sown at 60cm x 15cm produced higher growth, yield attributes, yield and economics. Amongdifferent nitrogen levels, application of 80 kg N ha-1 resulted in tallest plants and 60 kg N ha-1 produced higher drymatter production. Application of 100 kg N ha-1 produced higher leaf area and leaf area index, yield attributes,whereas, grain yield was higher with application of 60 kg N ha-1 and straw yield was higher with application of 80 kgN ha-1. Higher gross, net returns and B:C ratio was recorded with application of 40 kg N ha-1 compared to 60, 80 and100 kg N ha-1 which in turn comparable to each other